One move, two gains: commercial kickbacks suppression and corporate tax avoidance - Hu, Shiyang (Journal of business ethics, 2025)
This study uses China’s Medicinal Product Procurement Reform (MPPR) as an exogenous negative shock to commercial kickbacks for Chinese pharmaceutical firms and examines the causal effect of commercial kickbacks on corporate aggressive tax avoidance. Employing a staggered difference-in-differences approach, we find a significant reduction in tax aggressiveness among firms affected by the MPPR. Mechanism analysis reveals that the reform leads to a notable decline in treated firms’ kickback-related expenses, including abnormal entertainment and travel costs and average sales personnel salaries. In line with this mechanism, we find that the suppressive effects of the MPPR on tax aggressiveness vary depending on firms’ pressures, rationalization, and opportunities for avoiding tax. These results highlight that firms engaged in unethical practices like commercial kickbacks are more likely to adopt other forms of misconduct, such as aggressive tax avoidance, thus emphasizing the need to address unethical behavior at its root cause to mitigate its broader consequences.